Structure Evolution of Multi-Alloyed Iron Aluminides during Two-Step Annealing - Vodickova, Vera; Hanus, Pavel; Pazourkova Prokopcakova, Petra; Svec, Martin (Manufacturing Technology Journal, 2024)
The microstructure of single-phase (as-cast) and two-phase (after heat treatment processes) Fe3Al-based alloys doped with silicon, molybdenum, and vanadium/tungsten have been studied. The grain size and phase composition have been determined. The evolution of the secondary phase amount, morphology, and distribution during the heat treatment process has been investigated. Both alloys were heat treated at 1200°C/2 h and, subsequently, at 900 °C. For both alloys, the secondary phase formation started after heat treatment at 900°C /4h, and their amount depended on the annealing time. Vanadium atoms remain in the solid solution, while tungsten atoms partially participate in sec-ondary phase formation.
Keywords: Fe-Al-Si iron aluminides; Molybdenum; and vanadium/tungsten addition; Heat treatment